2016
DOI: 10.1007/s12178-016-9337-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of complex elbow fracture-dislocations

Abstract: Successful management of complex elbow fracture-dislocations requires, in part, recognition of the overall injury pattern, which can aid in the identification of concomitant bony and soft tissue injuries. Trans-olecranon fracture-dislocations are best treated surgically with stable anatomic restoration of the trochlear notch. Terrible triad elbow injuries are believed to be caused by a valgus posterolateral force. Although select terrible triad injuries can be managed non-operatively, the majority of injuries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 31 publications
(41 reference statements)
0
31
0
Order By: Relevance
“…There are several well-recognized fracture-dislocation injury patterns, and an understanding of these conditions is helpful to predict associated injuries and to guide treatment strategies. 42 Injury patterns include elbow dislocation associated with radial head or coronoid fracture or both fractures (terrible triad injury), Monteggia lesions or anterior olecranon fracture-dislocation, and posteromedial varus instability. They represent disruption injuries and not full dislocations because the opposing surfaces of the trochlea and ulna remain partially in contact.…”
Section: Complex Dislocationsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several well-recognized fracture-dislocation injury patterns, and an understanding of these conditions is helpful to predict associated injuries and to guide treatment strategies. 42 Injury patterns include elbow dislocation associated with radial head or coronoid fracture or both fractures (terrible triad injury), Monteggia lesions or anterior olecranon fracture-dislocation, and posteromedial varus instability. They represent disruption injuries and not full dislocations because the opposing surfaces of the trochlea and ulna remain partially in contact.…”
Section: Complex Dislocationsmentioning
confidence: 99%
“…These injuries are characterized by the disruption of the ulnohumeral joint and anterior displacement of the radial head relative to the capitellum, but the proximal radioulnar joint remains intact. 42 In these condi-tions surgery is necessary for a stable restoration of the greater sigmoid notch. 47…”
Section: Anterior Olecranon Fracture-dislocationmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9,10 Although simple posterior elbow dislocation can result from ligamentous injury (progressing lateral to medial from the LUCL to the MCL), several patterns of complex elbow dislocation must be recognized and managed appropriately to avoid recurrent instability, arthritis, stiffness, and pain. 6,[11][12][13] Among these complex dislocations, the so-called terrible triad injury (i.e., posterior elbow dislocation with radial head and ulnar coronoid process fractures) typically requires immediate surgical management with radial head arthroplasty and capsuloligamentous repair. 6 Similarly, Monteggia fracture-dislocation (proximal ulnar fracture with radial head dislocation) and posteromedial varus instability injury (shear fracture of the anteromedial facet of the coronoid process and disruption of the lateral collateral ligament complex) also typically require surgical fixation to maintain elbow stability.…”
Section: Elbowmentioning
confidence: 99%
“…The Monteggia injury includes bony and ligamentous disruption, and anatomical realignment of the ulna using plates and screws is key to reduction of the radial head while the origin of the LUCL can be repaired with sutures via tunnels in the lateral epicondyle or an anchor. 6,12 Multiple studies support the utility of computed tomography (CT) after an elbow dislocation event. For example, one retrospective study demonstrated fracture(s) in 96% of post-dislocation elbow CTs (most commonly involving the coronoid process); only 62% of the fractures were identified radiographically.…”
Section: Elbowmentioning
confidence: 99%